Host Cell Autophagy in Immune Response to Zoonotic Infections - Panagiotis Skendros; Ioannis Mitroulis (Clinical and Developmental Immunology)
Autophagy is a fundamental homeostatic process in which cytoplasmic targets are sequestered within double-membraned autophagosomes and subsequently delivered to lysosomes for degradation. Accumulating evidence supports the pivotal role of autophagy in host defense against intracellular pathogens implicating both innate and adaptive immunity. Many of these pathogens cause common zoonotic infections worldwide. The induction of the autophagic machinery by innate immune receptors signaling, such as TLRs, NOD1/2, and p62/SQSTM1 in antigen-presenting cells results in inhibition of survival and elimination of invading pathogens. Furthermore, Th1 cytokines induce the autophagic process, whereas autophagy also contributes to antigen processing and MHC class II presentation, linking innate to adaptive immunity. However, several pathogens have developed strategies to avoid autophagy or exploit autophagic machinery to their advantage. This paper focuses on the role of host cell autophagy in the regulation of immune response against intracellular pathogens, emphasizing on selected bacterial and protozoan zoonoses.